Analysis of Non-Linguistic Problems in Arabic Language Learning for Beginner Students in the Intensive Arabic Language Education at Islamic Universities - Masruhani, Hasna'i (Nurul Jadid University, 2023)
In learning Arabic, several problems will be found in its implementation, especially for beginner learners in Arabic. This problem consists of linguistic problems and non -linguistic problems. This study will focus on non-linguistic problems which include elements of motivation, teacher competencies, time and language environment. The purpose of this study is to explain and describe the problems or problems encountered during Arabic learning for novice students in the Arabic Intensive Program in State Islamic University of Surabaya. In this study using descriptive qualitative methods with data collection techniques using structured interviews with three students from class B-16 who incidentally have a lack of ability in Arabic language as evidenced by the results of the placement test, a one of the Arabic Language Teachers in class B-16 results This study shows that non -linguistic problems in learning Arabic consist of motivation and interest in learning, learning facilities, teacher competencies, learning methods, lack of time, and learning environment.